Pengaruh Latihan Aquatic Water Running Terhadap Peningkatan Kecepatan Berlari Pada Pemain Futsal - NARADA, Dewanta, Umi Budi Rahayu SST FT, M.Kes, Isnaini Herawati, SSt. FT, M. Sc (2015)
Narrow space requires the players to run faster in the game of futsal, because this is very important because it aims to win in the race for the ball with an opposing player and when defender breakthrough send feedback or feed the stomach in front of the player, the next player must run as fast as possible in order get the ball, also when a player is carrying the ball and no opponent who tried to catch, can be easily we leave when we have a good running speed. One solution is to increase the running speed futsal player is with aquatic exercise. Aquatic exercise evokes the elastic properties of muscle fibers and connective tissue in a way that allows the muscles to store energy during deceleration phases and releases energy during the acceleration period. This study aims to examine whether there is any difference between the effect of conventional exercise combined with running water aquatic exercise and conventional exercise on running speed futsal players. Experimental research design is, by design used one group pre - test - post-test. The amount of sample is 32 people, divided into two groups: conventional and conventional exercise training combined aquatic water running. Data were analyzed using the Wilcoxon rank test and Mann Whitney test. Results showed (1) there is the influence of conventional exercise combined with running water aquatic exercise on running speed futsal players (p - value = 0.001), (2) there is a conventional exercise influence on running speed futsal players (p - value = 0.001), and (3) there is a difference between the effect of conventional exercise combined with running water aquatic exercise and conventional exercise on running speed futsal players where conventional exercise combined with running water aquatic exercise has a better effect compared with conventional exercise.